peran media sosial dalam membangun harmonisasi keberagaman dalam perspektif agama islam: peran media sosial dalam membangun harmonisasi keberagaman dalam perspektif agama islam - karomah, isnah faridah uyun (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2024)
This article discusses how social media can build harmony and diversity. The development of social media has a crucial role in creating the harmonization of diversity. Social media can strengthen positive messages by presenting exciting content and building relationships that harmonize diversity in Indonesia. Based on this, the article raises the issue of how social media can be a forum for building harmonization of diversity in Indonesia, which aims to create unity and tolerance between religious communities. From this article, we can understand that social media is an effective tool for encouraging diversity. This article is studied using an intercultural communication perspective.